Dynamics Analysis of Credit Transmission on Foreign Bank Penetration in Indonesia - Mahjus Ekananda (University of Merdeka Malang, 2022)
Studies explore mode penetration bank foreign in transmission credit channel in Indonesia. ARDL-PMG is used for analyzing Office Bank branch Foreign (FOB) and Foreign Acquired Banks (FAB) on data panel bank-level, using the BI-7DR Days Reverse-repo rate and JIBR as monetary policy indicators. This study uses data on individual banks classified as FBO and FAB in Indonesia. The use of the ARDL-PMG model as an alternative to solve dynamic heterogeneous panels on credit channel problems in Indonesia. The main finding of this study proves that FBO and FAB show different credit channel transmission mechanisms in response to monetary policy. Studies also show that monetary policy contraction significantly impact towards FBO and FAB in Indonesia in the long-run. This studies due to the characteristics of Foreign Bank Branch Offices that are risk averse and have higher liquidity and Foreign Acquired Banks with higher capitalization. This characteristic causes the impact of contractionary monetary policy insignificant on FBO credit growth and FAB. The research has implications for financial and banking authorities to improve supervision over credit transmission at FBO and FAB due to differences in credit channel transmission mechanisms in response to monetary policy.